The book of lies [large type] - Meltzer, Brad (Grand Central Pub., 2008)
In 1932, Mitchell Siegel was killed by three gunshots to his chest. While mourning, his son dreamed of a bulletproof man and created the world's greatest hero: Superman. And like Cain's murder weapon, the gun used in this unsolved murder has never been found. Today in Fort Lauderdale, Florida, Cal Harper comes face-to-face with his family's greatest secret: his long-lost father, who's been shot with a gun that traces back to Mitchell Siegel's 1932 murder. But before Cal can ask a single question, he and his father are attacked by a ruthless killer tattooed with the ancient markings of Cain.--From publisher description.